IMPACT OF INCOME, CONSUMPTION, SAVING, AND NUMBER OF ZAKAT MANAGEMENT ORGANIZATIONS ON THE ZAKAT FUND COLLECTION - Deru R Indika; Sarah Nur Fauziyyah Himawan; Egi Arvian Firmansyah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
The good and responsible use of zakat funds can benefit the entire community. As the Muslim-majority country, Indonesia had the zakat potential of around 217 trillion rupiahs (in 2017). However, the realization of zakat fund collection was only 1.8% or around 4.1 trillion rupiahs. The same thing also happened primarily in the province of West Java, which could only collect zakat funds of around 2% of its entire zakat potential of 17.6 trillion rupiahs. This research aims at analyzing the factors affecting the collection of zakat funds in the cities of West Java. The data used in this research is the secondary data (from 2011-2017), acquired from the Central Bureau of Statistics (BPS), The Ministry of Religion, and BAZNAS (Nasional Zakat Agency). The data is analyzed using the Multiple Linear Regression Model and Generalized Least Squares (GLS) or Random Effect Method. The results of this research show that income, consumption, and the number of Zakat Management Organizations have a positive and significant effect on the zakat fund collection while saving has a negative and insignificant effect on zakat fund collection in West Java.